Application of adaptive fuzzy control to suppression vibration response of floating offshore wind turbine (Xibei Gongye Daxue Xuebao, 2021)
Floating offshore wind turbine is a complex rigid-flexible coupling nonlinear system, and the accurate dynamic model is difficultly established. Therefore, the wind-wave interference cannot be improved by adopting the conventional control strategy. In order to solve this problem, an adaptive fuzzy controller (AFC) is used to suppress the dynamic response of floating wind turbine. Two correction factors are introduced to optimize the fuzzy rule, and the traditional fuzzy controller (FC) is firstly obtained. Since the balance positions change and structural parameter perturbation of the wind turbine, an AFC is designed and validated. Finally, the suppression vibration responses ability of floating offshore wind turbine by using the different control strategies is studied under the random wind-wave disturbance and blade pitch control system coupling effect. The simulation results show that the tracking ability of the AFC to the target value is obviously higher than that of the FC; Comparing with the passive control strategy, the suppression vibration effect on the power spectral density (PSD) of the platform pitch (PFPI) motion peak can increase by 39.06% by adopting the AFC.